Two cases of chronic pancreatitis associated with anomalous pancreaticobiliary ductal union and mutation - Eun Sam Rho; Earl Kim; Hong Koh; Han-Wook Yoo; Beom Hee Lee; Gu-Hwan Kim (Korean Pediatric Society, 2013)
Chronic pancreatitis is a progressive inflammatory disease resulting from repeated episodes of acute pancreatitis that impair exocrine function and eventually produce endocrine insufficiency. Some causes of chronic pancreatitis appear to be associated with alterations in the serine-protease inhibitor, Kazal type 1 (SPINK1), cationic trypsinogen (PRSS1), and cystic fibrosis-transmembrane conductance regulator (CFTR) genes, or with structural disorders in the pancreaticobiliary ductal system, such as pancreatic divisum or anomalous pancreaticobiliary ductal union (APBDU). However, it is unusual to observe both genetic alteration and structural anomaly. Here, we report 2 cases with both APBDU and a mutation in the SPINK1 genes, and we discuss the implications of these findings in clinical practice.